The Role of The Physical and Social Environment for Physical Activity for College Students During the Covid-19 Pandemic - Bopp, Melissa; Wilson, Oliver W.A.; Elliott, Lucas D.; Holland, Kelsey E.; Duffey, Michele (Building Healthy Academic Communities Journal, 2021)
Background: The COVID-19 pandemic created significant disruptions for college students, impacting health and physical activity (PA). Changes to the PA environment presented many challenges for students. Purpose: To examine the influence of the physical and social environment on PA participation for college students during the onset of COVID-19 restrictions. Methods: This cross-sectional, mixed methods survey used an online questionnaire during the onset of COVID-19 restrictions with a volunteer sample of college students at a large university in the United States. Participants self-reported their demographics, PA level and environment for PA, and responded to an open-ended question about their PA participation during the pandemic. Correlations and independent samples t-tests examined relationships between PA and the environment. Qualitative data were scanned to identify overarching themes. Results: Participants (n = 395) were predominantly Non-Hispanic White and female. The neighborhood environment and access to PA equipment were associated with PA for both men and women. Major qualitative themes highlighted the role of the physical environment and PA. Participating in PA with friends and family was positively associated with PA for both men and women as well. Conclusions: This study provides insight on the importance of the social and built environment for encouraging and supporting PA among college students during the COVID-19 pandemic which may provide insight for distance education as higher education evolves.